Influence of health warnings present on cigarette packets, on motivation to quit smoking, among smokers in a slum of Kolkata - Dalal, Rajesh Kumar; Sarkar, Dipanwita; Tiwary, Narendra Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: The Government of India by National Health Policy 2017 has set the target of relative reduction in prevalence of current tobacco use by 15% and 30% by 2020 and 2025 respectively. The Union health ministry had notified to mandatory display new health warnings to be covering 85% of the principal display area on all tobacco products (1 April 2016). Methods: This was an observational descriptive study with cross sectional in design carried out at Baghbazar slum in Kolkata with objective to study the smoking pattern, knowledge about health warning symbols (HWS) on tobacco products among the study population and to assess their motivation to quit and influence of HWS on their motivation. A total 66 smokers were interviewed using predesigned and pre tested questionnaire and analysis done using SPSS version 1. Results: About 83.3% study subjects were presently smoking and they were smoking daily, about 10 cigarette and bidi was smoked daily (median) and median duration without smoking was 1 month. About 63.6% study subjects were highly motivated to quit smoking. Health warning was definitely motivating them to quit smoking (p=0.01) but it was not resulting in actual quitting smoking (p=1.000). The main reason for motivation for quitting smoking was self-health related factor (84.6%). Conclusions: Health warning on cigarette packets increased the awareness about ill effects of smoking and motivated the smokers to quit smoking but not compelling them to quit smoking. Mostly those who were motivated to quit smoking were actually thinking about quitting due to other reasons.